Nanofibers: where they are where we need them to be - Hromadko, Ludek; Rihova, Martina; Macak, Jan M. (Frontiers in Nanotechnology, 2025)
This perspective article focuses on polymeric and inorganic nanofibers and their synthesis. The reason for this material to be put in perspective is–with all the respect to those, who contributed to its development–it has not made it as far as people thought in past that it would and could. This article aims to put in perspective a summary and outlook, what remaining steps need to be done and overcome, so that these nanofibers become industrially viable and feasible to produce, and that end users can finally profit from their utilization in various applications.